Pengaruh Penggunaan Media Kartu Gambar Terhadap Minat Baca Anak Usia 4-5 Tahun di BKB PAUD As-Sholihin - komala; Mufassirul Alam (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study aims to determine the effect of using picture cards on the reading interest of children aged 4–5 years at BKB PAUD As-Sholihin. The low reading interest of early childhood children often becomes an obstacle to developing early literacy skills. Picture cards were chosen because they provide interesting, concrete visual stimulation and are appropriate to the characteristics of children. This study used a quasi-experimental method with a one-group pretest-posttest design. The research sample consisted of 27 children aged 4 to 5 years. Data were collected through observation using a reading interest assessment instrument. The results showed a significant increase in reading interest scores after being treated with picture cards. The average pretest score of 50,59 increased to 77,37 in the posttest. The t-test showed a significance value of 0.000 <0.05, so it can be concluded that picture cards have a positive effect on increasing children's reading interest.